2011
DOI: 10.1590/s0034-71672011000600002
|View full text |Cite
|
Sign up to set email alerts
|

Práticas de manejo do cateter central de inserção periférica em uma unidade neonatal

Abstract: The study aimed to describe the management of Peripherally Inserted Central Catheters insertion in neonates admitted at a neonatal intensive care unit of a private hospital, after implementation of the institutional protocol. An exploratory, quantitative descriptive study with prospective data collection was carried out. Data of 45 catheters insertion were analyzed. The rate of catheter's with elective removal was 63.8%, and catheter's complications rate was 30.8%. The most frequently complications were ruptur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
28

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 8 publications
1
7
0
28
Order By: Relevance
“…Considering the newborns' characterization (Table 1), there was a predominance of newborns (51.1%), who were born with gestational age between 28 and 36.6% (93%), with a average of 31.1 weeks (SD: 3.9, the minimum was 24.5 and the maximum 41.1), the weight between 1,000 and 1,499 g (35%), and below 1,000 g (32.1%), suitable for gestational age (67.9%), where the main diagnosis was the prematurity (87.6%). With regards to the characterization of the neonates still, in relation to the variables gestational age, birth weight and clinical diagnosis of hospitalization, the results found in this study corroborate with that described in the literature, [3][4]7,9 since the NICU researched is linked to the referral maternity from a university hospital and has high risk gestation cases.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Considering the newborns' characterization (Table 1), there was a predominance of newborns (51.1%), who were born with gestational age between 28 and 36.6% (93%), with a average of 31.1 weeks (SD: 3.9, the minimum was 24.5 and the maximum 41.1), the weight between 1,000 and 1,499 g (35%), and below 1,000 g (32.1%), suitable for gestational age (67.9%), where the main diagnosis was the prematurity (87.6%). With regards to the characterization of the neonates still, in relation to the variables gestational age, birth weight and clinical diagnosis of hospitalization, the results found in this study corroborate with that described in the literature, [3][4]7,9 since the NICU researched is linked to the referral maternity from a university hospital and has high risk gestation cases.…”
Section: Resultssupporting
confidence: 88%
“…Some authors report values for the central position above that found in this study, in relation to the tip position. 2,9 It is worth noting that the professionals of the research unit do not use standardization to determine the position of the tip, therefore, this classification can occur subjectively.…”
Section: Resultsmentioning
confidence: 99%
“…Essa infecção ocorre pela presença de microrganismos na ponta do cateter e na hemocultura (8) . Portanto, é fundamental ter conhecimento de que a maioria das infecções relacionadas ao cateter, resultam da contaminação do hub (canhão), do lúmem do cateter ou da solução infundida (16) , cabendo à equipe de saúde a responsabilidade pelas ações preventivas dessa infecção, visto que seu papel é fundamental no manuseio dos dispositivos intravenosos. Por isso, a ANVISA recomenda que todos os profissionais que lidam com o referido dispositivo tenham capacitação de alto nível, educação permanente, treinamento específico e avaliação sobre os conhecimentos das diretrizes institucionais voltadas para a prevenção, para o cuidado ético e para a segurança do processo assistencial.…”
Section: Discussionunclassified
“…14,[49][50][51] The most used type of silicone catheter was mono lumen. 10,14,49,51 Most punctured venous catheters were located in upper limbs, especially the basilic vein, and then the cephalic.…”
Section: Description Picc Use Categorymentioning
confidence: 99%